JILBAB DALAM KONSTRUKSI PEMBACAAN KONTEMPORER MUHAMMAD SYAHRÛR - Najitama, Fikria (Sunan Kalijaga State Islamic University & The Asia Foundation, 2014)
This article will discuss the thoughts of Muhammad Syahrur on the hijab. For Muhammad Syahrur, the veil is a matter of shame and embarrassment in custom, not a question of halal and haram. In his view, women should dress in accordance with the conditions, situations and local customs, so heavoided considering interference from either natural or social factors. This view is certainly different from that of the majority of commentators (mufassir) who think the veil is part of God’s commands associated with the issues of halal and haram. This study offers the thought of Muhammad Syahrur as an alternative in relation to the concept of the veil in the context of Indonesian society.